Factors contributing to medicine-related problems in adult patients with diabetes and/or cardiovascular diseases in Saudi Arabia: a qualitative study. Issue 11 (12th November 2017) - Al Hamid, Abdullah Mahdi; Ghaleb, Maisoon; Aljadhey, Hisham; Aslanpour, Zoe
Abstract : Objectives: To investigate the factors contributing to medicine-related problems (MRPs) among patients with cardiovascular diseases (CVDs) and/or diabetes in Saudi Arabia. Design: Qualitative semistructured interviews were conducted. Interviews were audio recorded then transcribed into Microsoft Word. The transcribed interviews were then imported into the qualitative analysis software NVivo where thematic analysis was applied. Thematic synthesis was achieved by coding and developing subthemes/themes from the findings of the interviews. Setting: Five healthcare centres in Najran, Saudi Arabia. Participants: 25 adult patients with diabetes and/or CVDs. Results: The study cohort included 16 men and 9 women with a median age of 61.8 years (40–85 years). Diabetes was the main condition encountered among 23 patients and CVDs were reported among 18 patients. Perceived factors leading to MRPs were of four types and related to: patient-, healthcare system-, clinical (condition-) and medicine-related factors. Patient-related factors were related to living situation, religious practices, diet/exercise and patients' behaviour towards the condition and medicines. Healthcare system-related factors comprised sources and availability of medicines, ease of access to healthcare system and patient satisfaction with healthcare providers. Clinical (condition-) related factors associated with both the knowledge and control over condition, and effects of the condition among medicines intake. Medicine-related factors included lack of knowledge about medicines and medicine use. Conclusions: The results of this study uncovered many factors associated with MRPs among patients with CVDs and diabetes in Saudi Arabia, especially in reference to lifestyle and medicine use. Improving communication with healthcare professional alongside the introduction of national clinical guidance would mitigate the unwanted health complications related to medicine use.